Liquiritin Attenuates Lipopolysaccharides-Induced Cardiomyocyte Injury via an AMP-Activated Protein Kinase-Dependent Signaling Pathway - Mou, Shan-Qi; Zhou, Zi-Ying; Feng, Hong; Zhang, Nan; Lin, Zheng; Aiyasiding, Xiahenazi; Li, Wen-Jing; Ding, Wen; Liao, Hai-Han; Bian, Zhou-Yan; Tang, Qi-Zhu (Frontiers in Pharmacology, 2021)
Background: Liquiritin (LIQ) is a traditional Chinese medicine that has been reported to regulate inflammation, oxidative stress and apoptotic cell death. However the beneficial effects of LIQ against lipopolysaccharides (LPS)-induced septic cardiomyopathy (SCM) has not been studied in detail. The primary goal of this study was to explore the effects of an LIQ in LPS-induced SCM model. Methods: Mice were pre-treated with LIQ for 7 days before they were injected with LPS (10mg/kg), a standardized murine model of SCM. Twelve hours following LPS injection, echocardiographic analysis was used to evaluate cardiac function. Thereafter, mice were sacrificed to collect hearts for molecular and histopathologic assays by RT-PCR, western-blots, immunohistochemical and terminal deoxynucleotidyl transferase nick-end labeling (TUNEL) staining analysis respectively. AMPKα2 knockout (AMPKα2-/-) mice were used to elucidate the mechanism of action of LIQ, and these studies were confirmed in vitro using of action of LIQ, and these studies were confirmed in vitro using neonatal rat cardiomyocytes (NRCM). Results: LIQ administration attenuated LPS-induced myocardial dysfunction and reduced mortality, based upon restoration of EF, FS, LVEDs, heart rate, dp/dt max and dp/dt min induced by LPS treatment. LIQ treatment also reduced TNFα, IL-6 and IL-1βmRNA expression, inhibited inflammatory cell migration, suppressed cardiac oxidative stress and apoptosis, and improved metabolism. Mechanistically, LIQ enhanced the phosphorylation of AMP-activated protein kinase α2 (AMPKα2) and decreased the phosphorylation of mTORC1, IκBα and NFκB/p65. Importantly, in AMPKα2 knockout model, the beneficial effects of LIQ were not observed, nor were they observed using an in vitro model in the presence of an AMPK inhibitor. Conclusion: We have clearly demonstrated that LIQ exerts its protective effects in an SCM model induced by LPS administration. LIQ reduced inflammation, oxidative stress, apoptosis and metabolic alterations via activation of an AMPKα dependent signaling pathway. Thus, LIQ might be a potential treatment or adjuvant for SCM treatment.